Current matched all perovskite tandem solar cells with low lead perovskites achieving 31.9% efficiency and enhanced stability - Navdeep Kaur; Jaya Madan; Asaithambi Perumal; Rahul Pandey (Scientific Reports)
Abstract Multilayer tandem solar cells emerge as a transformative solution, leveraging multiple absorber layers with optimized bandgaps to capture and convert a broader spectrum of sunlight. This layered architecture overcomes the efficiency limitations of single-junction solar cells by minimizing transparency and thermalization losses while maximizing photon utilization across the solar spectrum. Although hybrid perovskites have demonstrated exceptional photovoltaic performance, their dependence on organic components often results in stability challenges under varying environmental conditions. To mitigate this issue, all-inorganic perovskites have emerged as a robust alternative, offering enhanced thermal and moisture stability along with reliable long-term performance. In the proposed design, a sustainable approach is adopted using a tin-based, low-lead, all-inorganic CsPb0.75Sn0.25IBr2 (1.78 eV) for the top subcell absorber, paired with a lead-free double perovskite Cs2TiI6 (1.02 eV), in the bottom subcell, with the use of SCAPS − 1D simulator. Standalone analyses of the top and bottom subcells are conducted before tandem configuration implementation. Importantly, tandem design is optimized by investigating the current matching point by varying the absorber layer thicknesses (100–1000 nm). Illuminating the top subcell with the AM 1.5G spectrum and passing filtered light to the bottom subcell enables extensive light absorption and improved overall PCE. With a common current point at 16.83 mA/cm2 the tandem design attains a peak PCE of 31.93%, accompanied by a fill factor (FF) of 86.84% and an open-circuit voltage (VOC) of 2.18 V. These findings highlight the potential of this optimized tandem solar cell design to deliver high efficiency with enhanced stability, offering a promising pathway for sustainable and scalable photovoltaic technologies.